Design of the accelerator stand with the ECR-source for simulation experiments on the of radiation damage of the steels of the nuclear industry - Chalykh, B.B.; Kuybeda, R.P.; Kulevoy, T.V.; Ziyatdinova, A.V. (Вопросы атомной науки и техники, 2014)
The imitation experiments of irradiation resistivity for steels used in nuclear industry by heavy ion beams are promising demand for material properties investigation. The formation of the defects on the real-existing reactors is fraught with many difficulties such as a long-term session of exposure and induced radioactivity in samples. Simulation of radiation defects on accelerators of charged particles does not have such a drawback. To form radiation defects in matter, it is necessary to have beams of various ions with different energy. The concept of the test bench based on a ECR heavy-ion source for the imitation experiments of the materials resistance under irradiation is presented and discussed.